2017
DOI: 10.5465/ambpp.2017.14278abstract
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of the Implementation of Strategies in Latin American Firms’ Export Performance

Abstract: This study examines the relationships among competitive strategies (differentiation and costleadership), MO (market orientation), and export performance. We used a questionnaire survey of executives of manufacturing and service companies in Peru, Brazil, Mexico and Chile and employed a structural model equation to test the hypotheses and confirmatory factor analysis to develop the underlying multi-item constructs. We find that MO mediates the implementation of competitive strategies in export performance. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Narentheren and Haim (2014) conceptualization and operationalization of SCA measures with two dimensions were adopted, namely LCA and DFA due to the scale items concentrate on the primary elements of SCAs and "the required characteristics of unidimensionality, reliability and validity". Past researches conducted by Azaj et al (2020) and Heredia et al (2017) that were based on Narentheren and Haim (2014) measures further ascertained fairly high reliability coefficients in the export organization and banking sector, respectively. Hence, it further ascertained that Narentheren and Haim (2014)'s measurement is highly suited to be used in the electronics manufacturing organization, which experienced the similar fierce market competition setting.…”
Section: Measurementmentioning
confidence: 87%
See 1 more Smart Citation
“…Narentheren and Haim (2014) conceptualization and operationalization of SCA measures with two dimensions were adopted, namely LCA and DFA due to the scale items concentrate on the primary elements of SCAs and "the required characteristics of unidimensionality, reliability and validity". Past researches conducted by Azaj et al (2020) and Heredia et al (2017) that were based on Narentheren and Haim (2014) measures further ascertained fairly high reliability coefficients in the export organization and banking sector, respectively. Hence, it further ascertained that Narentheren and Haim (2014)'s measurement is highly suited to be used in the electronics manufacturing organization, which experienced the similar fierce market competition setting.…”
Section: Measurementmentioning
confidence: 87%
“…This paper is a novel research for Malaysian electronics industry survival and SCAs in post pandemic outbreak context as compared to the past researches conducted by Azaj et al (2020), Heredia et al (2017) and Naratheen and Haim (2014) that focuses on the populations in export organization and banking sector, hotel industry setting, respectively. The result of research would extensively contribute to the body of knowledge by validating the SCA measurements in Malaysian electronics industry context as measurement validations studies are barely found.…”
Section: Discussionmentioning
confidence: 99%